THERMAL CONDUCTIVITY OF SOME GRANITE SAMPLES - ABDULLAH, MOHD RIZAN (Universiti Teknologi Petronas, 2011)
This report discusses the research that has been done on order to understand Thermal Conductivity of Granite and starts to make a relationship on any occurrence in the reservoir Thermal conductivity is one of the important parameters that describe heat flow. The objective of this research is to measure thermal conductivity of several granite samples from two different locations which is from Ipoh-Lumut Highway and Lata Kinjang.and also to see the other parameters that affect thermal conductivity. Scientists from Newcastle University were investigating potential sources of geothermal energy, which is becoming increasingly popular in the search for lowcarbon energy resources. Granite can be particularly useful as it can be rich in radioactive elements that generate heat as they decay. Hopes have been raised for the viability of geothermal energy in the UK, after exploratory drilling in Weardale, County Durham, revealed record levels of permeability in granite. The scientists believe the find is not unique to the Weardale granite, as there are similar granites worldwide which may display equally high levels of permeability. This research focuses more on lab activities such as coring, thin section, XRD (X-ray Difrraction), XRF (X-ray fluorescence), Thermal Conductivity, Microscopy Polarization Image via Thin section and FE SEM.